Optimizing Digital Literacy Management: Synergy between Teachers and Parents in Society 5.0 - Ramadhani, Khalilah; Fachrurazi, Diana (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2023)
Education has now entered the era of society 5.0, where digital technology makes all human work easier. Digital technology is used by adults and children. Seeing that children are also active users of digital technology, it is necessary to provide an understanding of digital literacy by parents and teachers. So that the use of digital media is not misused by children and can prevent irregularities. To teach children about digital literacy, parents and teachers need to work together and work in synergy, not throwing responsibility at each other. This research uses a literature study or literature review approach to several sources such as research journals, scientific articles, and books. After that, the data obtained is viewed, then conclusions are drawn to gain new understanding. Content analysis techniques were used to conduct the research. The results of the study show that parents and teachers can work together in fostering children's digital literacy through smooth communication, schools provide online platforms for sharing, parent-teacher meetings, and parents' initiatives to contact teachers.